Solitary juvenile xanthogranuloma of temporal bone: a case report - Shu-ni Wang; Ji Lu (BMC, 2022)
Abstract Background Juvenile xanthogranuloma (JXG) is a kind of non-Langerhans cell histiocytosis, usually with skin lesions as the main manifestation. It rarely occurs in other tissues or organs and even more rarely is it found in the skull. Here, we report a case of xanthogranuloma derived from the temporal bone that was not present in any other parts of the body. Case presentation A 15-year-old boy had an unaccountable right migraine for 7 months. A mass with tenderness was located behind his right ear. The mass gradually increased in size, and his headache continued. Eventually, he came to our hospital for treatment. A computed tomography (CT) scan and magnetic resonance imaging (MRI) revealed a cystic solid mass in the right temporo-occipital region with skull destruction. The clinical diagnosis was haemangiopericytoma and skull-derived tumour. Haematological and biochemical results were as follows: alanine aminotransferase (ALT) 7 U/L; aspartate aminotransferase (AST) 12 U/L; basophil percentage (BASO%) 1.2%; normal coagulation. The patient was successfully treated with total surgical resection of the tumour. Postoperative histopathology examination showed xanthogranuloma, and his prognosis after surgery was good. Conclusions Because JXG rarely occurs in the skull and lacks typical imaging findings, an accurate diagnosis is difficult. The diagnosis of this disease mainly depends on pathological examination and immunohistochemistry. If feasible, many intracranial lesions can be cured through complete resection.